CREATING INCLUSIVE LEARNING ENVIRONMENTS: GENDER SENSITIVITY IN ISLAMIC EDUCATION CLASSROOMS - Nurfaisal (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2025)
This study explores the integration of gender sensitivity in Islamic education classrooms at the elementary level to foster inclusive learning environments. Using a qualitative case study approach, data were gathered through interviews with teachers and administrators, focus group discussions with students, classroom observations, and analysis of curricular materials. Findings reveal that although educators recognize the importance of gender equality grounded in Islamic principles, traditional gender norms continue to influence curriculum content and classroom interactions, limiting the full realization of inclusive practices. Female representation in teaching materials remains minimal, and subtle gender biases persist in student participation and teacher engagement. Nonetheless, there is an emerging commitment among educators to adopt more gender-sensitive approaches, supported by efforts to include alternative narratives and role models. The study underscores the need for comprehensive curriculum reform, professional development, and community involvement to create genuinely inclusive Islamic education environments that respect both religious values and gender equity.